2013
DOI: 10.1002/pits.21712
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Building: Evidence‐based Practice and Adolescents on the Autism Spectrum

Abstract: Empirical research in the treatment of autism spectrum disorders (ASDs) has resulted in the identification of numerous evidence-based interventions (EBIs). Adolescents with an ASD are faced with unique academic challenges, complex social environments, and physiological changes. They often require interventions to aid in acclimating to their evolving social environments and physical changes. One of the many challenges for practitioners working with adolescents is turning research findings into practice. We prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…However, Kratochwill's () report on the use of EBP by school psychologists suggested that many of them have not received training and supervision in EBP, many faculty who train psychologists are not well prepared to teach evidence‐based interventions, and many practicing psychologists involved in supervising school psychology graduate students do not have training in a wide range of such interventions. Much attention has been dedicated to the use of EBP among other special education professionals (Cook, Tankersley, & Harjusola‐Webb, ; Rue & Knox, ; Spek, Wieringa‐de Waard, Lucas, & Dijk, ). There is increased attention devoted to school psychologists’ use of EBP; however, empirical findings in this area are lacking.…”
mentioning
confidence: 99%
“…However, Kratochwill's () report on the use of EBP by school psychologists suggested that many of them have not received training and supervision in EBP, many faculty who train psychologists are not well prepared to teach evidence‐based interventions, and many practicing psychologists involved in supervising school psychology graduate students do not have training in a wide range of such interventions. Much attention has been dedicated to the use of EBP among other special education professionals (Cook, Tankersley, & Harjusola‐Webb, ; Rue & Knox, ; Spek, Wieringa‐de Waard, Lucas, & Dijk, ). There is increased attention devoted to school psychologists’ use of EBP; however, empirical findings in this area are lacking.…”
mentioning
confidence: 99%